Impact of pharmacogenetics on aspirin resistance: a systematic review - Gustavo Figueiredo da Silva; Bruno Mattei Lopes; Vinicius Moser; Leslie Ecker Ferreira (Arquivos de Neuro-Psiquiatria)
Background Pharmacogenetics promises better control of diseases such as cardiovascular disease (CVD). Acetylsalicylic acid, aspirin, prevents the formation of an activating agent of platelet aggregation and vasoconstriction, and it is used to prevent CVD. Nevertheless, patients may have treatment failure due to genetic variants that modify the metabolism of the drug causing aspirin resistance (AR). Objectives To realize a systematic literature review to determine the impact of genetic variants on AR. Methods Articles published in the MEDLINE/PubMed, Cochrane, Scopus, LILACS, and SCIELO databases were systematically screened. A total of 290 articles were identified and 269 articles were excluded because they did not comply with the previously established inclusion criteria. A total of 20 case-control studies and 1 cohort was included. Results The genetic variants rs1126643 (ITGA2), rs3842787 (PTGS1), rs20417 (PTGS2), and rs5918 (ITGB3) were the most studied. As for relevance, of the 64 genetic variants evaluated by the articles, 14 had statistical significance (p < 0.05; 95% confidence interval [CI]) in at least one article. Among them, the following have had unanimous results: rs1371097 (P2RY1), rs1045642 (MDR1), rs1051931 and rs7756935 (PLA2G7), rs2071746 (HO1), rs1131882 and rs4523 (TBXA2R), rs434473 (ALOX12), rs9315042 (ALOX5AP), and rs662 (PON1), while these differ in real interference in AR: rs5918 (ITGB3), rs2243093 (GP1BA), rs1330344 (PTGS1), and rs20417 (PTGS2). As study limitations, we highlight the nonuniform methodologies of the analyzed articles and population differences. Conclusion It is noteworthy that pharmacogenetics is an expanding area. Therefore, further studies are needed to better understand the association between genetic variants and AR.